Diammonium glycyrrhizinate preparation for liver function recovery in chronic hepatitis B in China: a meta-analysis with trial sequential analysis - Liu, Yibo; Guo, Wenfang; Li, Minhui (Current pharmaceutical design, 2022)
The treatment of chronic hepatitis B (CHB) comprises a global medical problem, and the first-line clinical drugs have obvious shortcomings. The use of the plant extract diammonium glycyrrhizinate (DG) in food and medicine has gradually widened because of its safety and effectiveness. In clinical practice, DG is mainly used for liver-disease treatment, but DG intervention for CHB lacks systematic-based evidence. The included randomized controlled trials were analyzed by comparator and control respectively for alanine aminotransferase (ALT), aspartate transaminase (AST), and total bilirubin (TBIL) levels, hepatitis B virus DNA negative conversion ratio, and total effective rate, and subgroup analysis was conducted for intervention time, intervention dosage form, comparator drug, and combination drug, among others. Trial sequential analysis was used to verify the results. DG could effectively reduce ALT, AST, TBIL, and other liver-function indexes and had a definite effect on liver-function recovery. From the beginning of intervention to 3 months, the effect was significantly better than that of conventional treatment. Compared with other drugs, different dosage forms had differences in efficacy, and DG enteric-coated capsules and injections were lower than compound glycyrrhizin and magnesium isoglycyrrhizin. Meanwhile DG capsules had no significant difference with them. Meanwhile, trial sequential analysis of the main results confirmed the reliability of the conclusion. To our knowledge, this was the first relatively complete meta-analysis and systematic evaluation of the efficacy of DG intervention for CHB; liver-function recovery was discussed in the context of traditional Chinese medicine thinking, and DG's therapeutic effect in CHB was defined.